AKUNTABILITAS TRANSPARANSI PENGELOLAAN BOS DALAM OPTIMALISASI MUTU PENDIDIKAN - Sartika, Dian; Masduki, Masduki; Rochimah, Heni (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine transparency in the management of Bantuan Operasional Sekolah (BOS) in Indonesia, which is considered as one of the determining factors for the success of the program. Transparency in the management of BOS funds can increase public and stakeholder trust, and support improvements in the quality of education. This study uses a qualitative approach with a case study method to explore the practice of transparency in the management of BOS funds in several schools. Data were collected through interviews with school principals, treasurers, school committee members, and analysis of financial report documents. The results of the study indicate that the publication of financial reports openly increases public trust, but challenges related to infrastructure and access to technology in certain areas need to be addressed. In addition, cooperation between the government, schools, and the community is essential to ensure effective use of funds and equal distribution of education quality. This study concludes that transparency in the management of BOS funds has a significant role in improving the quality of education in Indonesia.